Analisis Pengaruh Pengetahuan Investasi, Motivasi, Modal Minimal Dan Persepsi Risiko Terhadap Minat Mahasiswa Berinvestasi Di Pasar Modal (Studi Kasus Mahasiswa FEB Universitas Dharma Andalas Angkatan 2019-2021) - Ratnawati Raflis Raflis; Syerli Arlianti Arlianti (CV. ITTC INDONESIA, 2023)
This study aims to determine the effect of investment knowledge, motivation, minimum capital investment, and perceived risk on students' interest in investing in the capital market. The focus of this research is focused on students. The type of research used is a type of quantitative research. The population in this study were all students of the Faculty of Economics and Business, Dharma Andalas University who had attended financial management 1 courses. The sampling technique in this study used a simple propositional random sampling. The number of samples is 261 respondents. Data was collected through a questionnaire. The results showed that investment knowledge had a positive and significant effect on students' interest in investing in the capital market, motivation, capital had a and significant effect on students' interest in investing in the capital market, minimal capital had a and significant effect on students' interest in investing in the capital market and Perceived risk has a and significant effect on students' interest in investing in the capital market. Keywords: Investment Knowledge, Motivation, Minimum Capital, and Perceived Risk